2020
DOI: 10.21203/rs.3.rs-133452/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Relationship of Anti-Mullerian Hormone in Polycystic Ovary Syndrome Patients With Different Subgroups

Abstract: Purpose To explore the value of anti-Mullerian hormone (AMH) in polycystic ovary syndrome (PCOS) patients for different phenotype and age, and identify the relationship between the hyperandrogenism (HA) and polycystic ovary morphology (PCOM) in Chinese cohort.Methods A total of 2262 women (1631 with PCOS and 631 health controls) were enrolled. The serum AMH and total testosterone (TT) were analyzed, compared the AMH level of each subgroup and evaluated the value of each phenotype and age group of PCOS.Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Androgens increase GC FSH receptors (FSHR), and increased FSH action stimulates AMH expression from growing follicles in PCOS 65,67 . Higher AMH levels were observed in anovulatory and hyper‐androgenic women with PCOS compared with normo‐androgenic women 67,68 . In women, AMH levels better predicted oligo/amenorrhoea than AFC 69 .…”
Section: Introductionmentioning
confidence: 99%
“…Androgens increase GC FSH receptors (FSHR), and increased FSH action stimulates AMH expression from growing follicles in PCOS 65,67 . Higher AMH levels were observed in anovulatory and hyper‐androgenic women with PCOS compared with normo‐androgenic women 67,68 . In women, AMH levels better predicted oligo/amenorrhoea than AFC 69 .…”
Section: Introductionmentioning
confidence: 99%
“…In our investigation, we discovered that the patient's age might predict AMH levels and a substantial negative connection, comparable to Ran et al's (2021) results, who found similar alterations in a healthy control group. 24 However, another research found comparable alterations in healthy young females but no link in PCOS people. 25 We also discovered a link between blood pressure and AMH.…”
Section: Discussionmentioning
confidence: 97%